2011
DOI: 10.1007/s12192-010-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 is acute phase reactant: response elicited by tumor treatment with photodynamic therapy

Abstract: Oxidative stress in photodynamic therapy (PDT)-treated tumor cells is known to instigate a strong upregulation of the expression of heat shock proteins. However, the treatment of mouse Lewis lung carcinoma (LLC) cells with Photofrin™ PDT resulted in the upregulation of heat shock protein 70 (Hsp70) gene not only in these cells but also in co-incubated untreated Hepa 1-6 cells. To investigate whether this phenomenon extends in vivo, LLC tumors growing in C57BL/6 mice were treated with Photofrin™ PDT. The tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
(53 reference statements)
1
22
0
2
Order By: Relevance
“…2). Since cytoplasmic HSP70 could translocate onto the cell surface after PDT treatment [25,26], neutralization of HSP70 blocked AC‐induced expression of NO production in macrophages. These results suggest that the translocated HSP70 from AC, which is responsible for the upregulation of iNOS expression in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…2). Since cytoplasmic HSP70 could translocate onto the cell surface after PDT treatment [25,26], neutralization of HSP70 blocked AC‐induced expression of NO production in macrophages. These results suggest that the translocated HSP70 from AC, which is responsible for the upregulation of iNOS expression in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…immune responses and may play a major role in maintaining immune homeostasis (Wachstein et al 2012). In addition, HSP70 has been suggested to exert its cytoprotective action by protecting mitochondria and by interfering with stressinduced apoptotic programming (Merchant and Korbelik 2011). Quantitative studies have confirmed numerous detection methods for HSP70, and HSP70 has been associated with various nondisease and disease conditions, demonstrating its clinical significance.…”
mentioning
confidence: 97%
“…HSP70 is also a member of the molecular chaperone family, which is involved in protecting cells against various types of stress. In addition, HSP70 has a protective role in tissue injury: it is produced in the liver and spleen as an acute-phase reactant and is released into the circulation to facilitate the disposal of dying cells (Merchant and Korbelik 2011). HSPs have been reported to play important roles in the activation and maturation of DCs (Tsan and Gao 2009).…”
mentioning
confidence: 99%
“…In our studies on the role of HSP70 in tumor PDT response, we discovered that HSP70 gene becomes upregulated in the liver and spleen of mice bearing PDT-treated tumors 22 . Our hypothesis that glucocorticoid hormones are responsible for this effect is now supported by two findings.…”
Section: Evidence Of the Involvement Of Glucocorticoids In Tumor Pdt mentioning
confidence: 98%